Outer membrane proteins from Legionella pneumophila serogroups and other Legionella species. - Hindahl, M S (1986)
Outer membranes were isolated from eight serogroups of L. pneumophila and five other Legionella species. The protein composition of the membranes was characterized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. A single, disulfide stabilized protein with a molecular size of 29,000 to 30,000 daltons was found to be the major outer membrane protein (MOMP) of all the serogroups. The equivalent of the L. pneumophila MOMP was not observed in any of the other Legionella species examined. Silver staining of sodium dodecyl sulfate-polyacrylamide gel electrophoresis gels revealed distinctive patterns for each serogroup and other Legionella species that were not observed by staining with Coomassie blue and may result from the presence of lipopolysaccharide in the membrane preparations. The MOMP from serogroup 1 was isolated by exposing crude peptidoglycan to detergent in the presence of heat and reducing agent and was found to be tightly associated with lipopolysaccharide. Antibodies to this complex were used to probe the outer membranes of the remaining, L. pneumophila serogroups and other Legionella species by Western blotting. Serogroup 1 anti-MOMP antibodies were found to react with the MOMP from the remaining seven serogroups examined, whereas antibodies directed against the lipopolysaccharide of serogroup 1 only reacted with lipopolysaccharide from two of the remaining seven serogroups.